Ewing sarcoma of the bone in children under 6 years of age. - Maria Antonietta De Ioris (PLoS ONE, 2013)
BACKGROUND: Ewing Sarcoma Family Tumours (ESFT) are rare in early childhood. The aim of this study was to report the clinical characteristics and outcome of children under 6 years of age affected by ESFT of the bone in Italy. METHODS: The records of all the children diagnosed with osseous ESFT in centres members of the Associazione Italiana di Ematologia ed Oncologia Pediatrica (AIEOP) from 1990 to 2008 were reviewed. The Kaplan-Meier method was used for estimating overall and progression-free survival (OS, PFS) curves; multivariate analyses were performed using Cox proportional hazards regression model. RESULTS: This study includes 62 patients. An axial primary localization was present in 66% of patients, with the primary site in the chest wall in 34%. Fourteen (23%) patients presented metastatic disease. The 5-year OS and PFS were 73% (95% confidence interval, CI, 58-83%) and 72% (95% CI 57-83%) for patients with localized disease and 38% (95% CI 17-60%) and 21% (95% CI 5-45%) for patients with metastatic disease. Metastatic spread, skull/pelvis/spine primary localization, progression during treatment and no surgery predicted worse survival (P<0.01), while patients treated in the last decade had better survival (P = 0.002). In fact, the 5-year OS and PFS for patients diagnosed in the period 2000-2008 were 89% (95% CI 71-96%) and 86% (95% CI 66-94%), respectively. CONCLUSION: The axial localization is the most common site of ESFT in pre-scholar children. Patients treated in the most recent period have an excellent outcome.